2014
DOI: 10.1155/2014/832736
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Insulin-Producing Cells from Human Bone Marrow-Derived Mesenchymal Stem Cells: Comparison of Three Differentiation Protocols

Abstract: Introduction. Many protocols were utilized for directed differentiation of mesenchymal stem cells (MSCs) to form insulin-producing cells (IPCs). We compared the relative efficiency of three differentiation protocols. Methods. Human bone marrow-derived MSCs (HBM-MSCs) were obtained from three insulin-dependent type 2 diabetic patients. Differentiation into IPCs was carried out by three protocols: conophylline-based (one-step protocol), trichostatin-A-based (two-step protocol), and β-mercaptoethanol-based (three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 38 publications
(45 reference statements)
2
35
0
Order By: Relevance
“…This method was chosen in view of its simplicity and the short duration required for its completion [14]. The yield of IPCs was modest and comparable among both types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…This method was chosen in view of its simplicity and the short duration required for its completion [14]. The yield of IPCs was modest and comparable among both types of cells.…”
Section: Discussionmentioning
confidence: 99%
“…e essential feature of this method is the use of TSA and GLP-1. Evidence showed that TSA can result in the di erentiation of bone marrow cells into IPCs in the presence of high glucose concentrations and GLP-1 [10,27,28]. e modi ed protocol entails adding activin-A, CHIR99021 and wortmannin during the initial phase of di erentiation.…”
Section: Immuno Uorescencementioning
confidence: 99%
“…In addition to the report by Rui Wei et al [122], Mahmoud M.Gabr et al [123] compared three IPS protocols involved in the human bone marrow derived mesenchymal stem cells (HBM-MSC) production. The first protocol was the one-step protocol.…”
Section: Mirnasmentioning
confidence: 99%